Metastatic Squamous Cell Carcinoma Component from an Adenosquamous Carcinoma of the Lung with Identical Epidermal Growth Factor Receptor Mutations - Jarred Burkart; Konstantin Shilo; Weiqiang Zhao; Efe Ozkan; Amna Ajam; Gregory A. Otterson (Case Reports in Pulmonology)
The case reported is a young “light” ex-smoker who initially had a localized adenosquamous carcinoma bearing an epidermal growth factor receptor (EGFR) sensitizing mutation. He first recurred six months after initial treatment within the brain with a pure squamous histology and the same EGFR mutation. Surgical resection and radiation rendered him disease-free. Subsequent isolated recurrence within the lung eighteen months later was a pure adenocarcinoma, again with the same identified EGFR mutation. These histologic changes (from adenosquamous to pure squamous to pure adenocarcinoma) have been described but not before in the absence of any selection pressure with EGFR tyrosine kinase inhibitors. This case points out the histologic “flexibility” of EGFR mutant lung cancers and the importance for appropriate molecular testing in nonsmokers with lung cancer of any histologic type.